A LITERACY STRENGTHENING TRAINING for LITERACY and WRITING GRADE ELEMENTARY SCHOOL TEACHERS in SORONG REGENCY - Yeni Witdianti; Nur salim (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2020)
Insert your abstract text, maximum 250 words providing trial information under the following sections. First, background. Provide context or background for the study and state the study’s primary objective or hypothesis in 1–2 sentences. Also, please explain the previous research/programf what other people do or what you have done before. Author include hypothesis (if any) which explained the tentative of result. Second, methods. Describe the basic procedures used during the study, including selection of study subjects and observational and analytical methods. Define the primary outcomes that were measured for each group of subjects about implementation of community engagement. Third, results and discussion. Summarize the main findings, including specific effect sizes and their statistical significance, if possible. Include (if relevant) the number of participants in each group, the primary outcome for each group, and any significant adverse events or side effects. Also, please explain relation between your theory and your result in your program. Fourth, conclusion. In 1–2 sentences, state the principal conclusions, emphasizing new and important aspects of the study or observations in aspect of community engagement. Also, mention the recommendation from your manuscript related about community engagement.